Sistema fotovoltaico para suministro de energía eléctrica en vivienda aislada - Lasluisa Morocho, Diego Hernán (2019)
The implementation of a photovoltaic system in an isolated house of the Andracas sector, Juan Montalvo Parish, Latacunga Canton was conducted from to supply it with electrical energy. To favor the economy and the comfort of that dwelling, whose location, in a place far from the electricity distribution network system, makes it very difficult to supply it with energy. The implementation was made based on the data collection by the solar radiation measurement equipment that is presented at the site, the respective analysis and comparison with the data obtained from “NASA” portal, too with the purpose of sizing the necessary elements that make up the system such as photovoltaic panels, batteries, charge regulator, inverter and its due protections against currents and voltages, which are unfavorable aspects that could endanger the other equipment in the system. The entire system contributes fully to the efficient and safe supply of electricity, even more with the advantage that the photovoltaic system is friendly to the environment and the electrical equipment needed for its implementation and connection of equipment is lower compared to the conventional electrical network.